2012
DOI: 10.1103/physrevstab.15.054201
|View full text |Cite
|
Sign up to set email alerts
|

Microbunch dynamics and multistream instability in a heavy-ion synchrotron

Abstract: For the operation as an injector for the FAIR project, the heavy-ion synchrotron (SIS) has to deliver intense and high quality ion bunches with a high repetition rate. One requirement is that the initial momentum spread of the injected coasting beam should not exceed the limit set by the available SIS rf bucket area. Furthermore, the Schottky spectrum should be used to routinely measure the momentum spread and revolution frequency directly after injection in order to adjust the rf settings. During the transver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The experiments presented here expand the parameter range of the GSI experiments [8][9], with bunch lengths reaching up to 41 times longer than the pipe diameter and 300 times longer than the beam radius at its minimum. Although this work focuses on a single expanding bunch, the physics can be extended to multi-bunch injection [7,10] or to longitudinal stacking of short rectangular bunches in a linac.…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The experiments presented here expand the parameter range of the GSI experiments [8][9], with bunch lengths reaching up to 41 times longer than the pipe diameter and 300 times longer than the beam radius at its minimum. Although this work focuses on a single expanding bunch, the physics can be extended to multi-bunch injection [7,10] or to longitudinal stacking of short rectangular bunches in a linac.…”
mentioning
confidence: 80%
“…In the early 1990s, Hofmann applied a particle-in-cell (PIC) code to simulate the electrostatic coupling that occurs as a multi-bunch beam overlaps, its velocity space mixes, and its phase space filamentary structure disappears [7]. A recent experimental observation of the multi-stream instability at the GSI Helmholtz Centre for Heavy Ion Research (GSI) revealed turbulent current spectra that were believed to be caused by the multi-stream instability of overlapping multiple bunches [8][9]. This paper extends previous work [7][8][9] by examining the dynamic non-linear elongation of a single bunch with a given initial length, predicting the time at which the overlapping beam segments become unstable, and determining the range of parameters for which instability appears.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the SIS18 the microbunches injected from the UNILAC with 36 MHz debunch, filament and form a coasting beam within a few turns. During debunching the longitudinal space charge force of the intense microbunches leads to an increases of the final momentum spread [6]. In this study we will first discuss optimum multi-turn injection schemes for low intensities.…”
Section: Introductionmentioning
confidence: 99%